Shear deformation characteristics under tensile stress during forming of tubular braided fabrics. (April 2023) - Li, Jinlei; Hamila, Nahiène; L'Hostis, Gildas; Wang, Peng
Abstract: Tubular braids with a hollow structure are widely used in the manufacturing of textile composites. As the dominant behavior during the forming of such fabrics, their mechanical responses under an axial tensile load have been investigated. Their complex behavior consisted of three main parts: non-homogenous in-plane shearing, pure yarn extension, as well as a combination of in-plane shearing and yarn extension. A "locking structure" was proposed as a sign of the structural damage and an analytical model was developed to describe the relationships of shear angle/shear moment and shear angle/shear load based on unit cells. The non-uniform shear deformation field, depending only on the global tensile deformation and the axial position, was well demonstrated by the analytical approach. We believe that the experimental and analytical approaches presented herein will improve the understanding of braided fabric forming and help advance the numerical simulation of this process.